Margaret Barrington interviewed by Rosslyn Finn for the Australia 1938 oral history project - Barrington, Margaret, 1915-; Finn, Rosslyn; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Barrington speaks of her family background; family life growing up in Paddington, Sydney; her parents' Scottish background and influence; family lifestyle; her children and marriage.
Transcript unavailable.
Working duplicate unavailable.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Keywords: Barrington, Margaret, -- 1915- -- Interviews; Women -- New South Wales -- Biography; Women -- New South Wales -- Social conditions -- 1901-1945.; Paddington (N.S.W.) -- Social conditions